Fault tolerant multicontrollers for nonlinear systems: A real validation on a chemical process - Mejdi, Sondess; Messaoud, Anis; Ben Abdennour, Ridha (Zielona Góra: Uniwersytet Zielonogórski)
An active sensor fault tolerant controller for nonlinear systems represented by a decoupled multimodel is proposed. Active fault tolerant control requires accurate fault estimation. Thus, to estimate both state variables and sensor faults, a discrete unknown input multiobserver, based on an augmented state multimodel, is designed. The multiobserver gains are computed by solving linear matrix inequalities with equality constraints.
Keywords: multicontroller; experimental validation; transesterification reactor; discrete unknown input multiobserver; fault tolerant control; sensor fault estimation